Biomimetic stem cell delivery composite hydrogel for bone and preparation method and application thereof

CN122624759BActive Publication Date: 2026-10-20QINGDAO UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611104895.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-20
Estimated Expiration
2046-07-24

AI Technical Summary

Technical Problem

然而,目前尚缺乏能够利用骨缺损区域生理性负荷作为触发信号,原位响应性释放MSCs,并与仿生矿化基质有机整合为一体的骨修复材料体系

Benefits of technology

本发明通过构建“中性微凝胶-成骨基质”分离式结构,将MSCs预先庇护于具有可调节膜特性的微凝胶隔室中,有效避免了传统直接包封方法中交联剂、剪切应力及过早分化信号对细胞的损伤,在静态储存和植入初期显著维持了MSCs的高活性。在力学刺激后,微凝胶膜响应性破裂,原位释放MSCs,实现了细胞保护与原位递送的时空分离与协同。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122624759B_ABST
    Figure CN122624759B_ABST
Patent Text Reader

Abstract

The application discloses a kind of bone biomimetic stem cell delivery composite hydrogel and its preparation method and application, and the composite hydrogel includes: osteogenic bone mimic matrix, which is a hydrogel with crosslinked network structure;And neutral microgel dispersed in the inside of the osteogenic bone mimic matrix;Neutral microgel is the microsphere with membrane structure formed by sodium alginate by ion crosslinking, its inside carries mesenchymal stem cells, and is configured to be ruptured when being subjected to mechanical stress exceeding its compression rupture threshold, release mesenchymal stem cells.The application constructs "neutral microgel-osteogenic matrix" isolated structure, and MSCs is pre-sheltered in microgel compartment with adjustable membrane characteristics, and the high activity of MSCs is significantly maintained in static storage and implantation initial stage.After mechanical stimulation, microgel membrane responds and ruptures, and MSCs are released in situ, which realizes the space-time separation and cooperation of cell protection and in-situ delivery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of biomedical technology, and in particular to a bone biomimetic stem cell delivery composite hydrogel, its preparation method, and its application. Background Technology

[0002] Satisfactory repair of critically sized bone defects remains challenging because successful bone regeneration is not merely about filling the defect; it requires an ideal functional construct that simultaneously provides mechanical support, maintains the survival of osteogenic progenitor cells, mediates cell-matrix adhesion, regulates mineral deposition, and synchronizes with the mechanical environment the bone experiences during healing. Mesenchymal stem cell (MSC)-based strategies are highly attractive because MSCs can directly participate in osteogenic processes and promote tissue repair through paracrine effects. However, their regenerative efficacy largely depends on the matrix composition, the mechanical environment of the cells, and the timing of exposure to osteogenic signals.

[0003] In existing technologies, many cell-loaded hydrogels are prepared by directly mixing cells into a precursor solution or by pre-culturing cells in vitro before implantation. While these methods are simple to operate, they may expose MSCs to shear stress, chemical cross-linking, temperature changes, and premature differentiation signals during preparation, thus affecting cell viability and function. Furthermore, these methods assume that a single, homogeneous matrix can both protect cells during preparation and provide a mature osteogenic microenvironment after implantation, which differs significantly from the physiological processes of bone repair in vivo. A more physiologically compliant design approach is to separate these tasks: first, shelter MSCs in independent compartments that maintain cell viability and allow them to retain their differentiation potential; then, when the construct is stimulated by mechanical signals related to weight-bearing or tissue repair, the MSCs are released into an osteogenic-inducible matrix at the appropriate time.

[0004] Numerous studies have confirmed that cyclic loading, matrix stiffness, and topological signals can all influence the osteogenic differentiation direction of MSCs. However, there is currently a lack of bone repair material systems that can utilize the physiological load of the bone defect area as a trigger signal to release MSCs in situ and organically integrate them with a biomimetic mineralized matrix. Summary of the Invention

[0005] The purpose of this invention is to address the shortcomings of existing technologies by providing a bone biomimetic stem cell delivery composite hydrogel, its preparation method, and its application.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect is to provide a stress-activated bone biomimetic stem cell delivery composite hydrogel, comprising: an osteogenic bone mimic matrix, which is a hydrogel with a cross-linked network structure; and a neutral microgel dispersed within the osteogenic bone mimic matrix; wherein the neutral microgel is a microsphere with a membrane structure formed by ionic cross-linking of sodium alginate, which carries mesenchymal stem cells and is configured to rupture the membrane and release the mesenchymal stem cells when subjected to mechanical stress exceeding the compression rupture threshold of the neutral microgel.

[0007] Furthermore, the osteogenic bone-mimicking matrix comprises hyaluronic acid, osteopontin, polyvinyl alcohol, nano-hydroxyapatite, bone morphogenetic protein-2, and adipic acid dihydrazide.

[0008] Furthermore, the osteogenic bone-mimicking matrix is ​​formed by cross-linking hyaluronic acid modified with osteopontin and adipic acid dihydrazide through amide bonds to form a cross-linked network. Polyvinyl alcohol is physically entangled in the cross-linked network and the network structure is further stabilized by hydrogen bonds. Nano-hydroxyapatite and bone morphogenetic protein-2 are dispersed and loaded in the cross-linked network.

[0009] Furthermore, the neutral microgel has a film thickness of 8-25 μm and a compression fracture threshold of 15-100 kPa.

[0010] Furthermore, the neutral microgel constitutes 5-15% by mass in the osteogenic bone-simulating matrix.

[0011] The second aspect is to provide a method for preparing the aforementioned stress-activated bone biomimetic stem cell delivery composite hydrogel, comprising the following steps: Step 1, preparing neutral microgels: a mixed suspension of sodium alginate solution and mesenchymal stem cell suspension is extruded through a microfluidic device into a crosslinking bath containing Ca-EDTA complex, and a neutral microgel containing mesenchymal stem cells is formed through ionic crosslinking, followed by washing and centrifugation for collection; Step 2, preparing osteogenic bone-mimicking matrix precursor solution; Step 3, constructing the composite hydrogel: the neutral microgel collected in Step 1 is dispersed in the osteogenic bone-mimicking matrix precursor solution in Step 2, injected into a mold, and crosslinked to form the bone biomimetic stem cell delivery composite hydrogel.

[0012] Further, in step one, the concentration of the sodium alginate solution is 2.0-3.0 g / 100mL, the flow rate of the dispersed phase extruded by the microfluidic device is 50-100μL / min, and the residence time in the crosslinking bath is 30-60s, so as to control the film thickness and compression rupture threshold of the neutral microgel.

[0013] Further, in step two, the preparation of the osteogenic bone matrix precursor solution includes: preparing a hyaluronic acid solution in phosphate buffered saline, activating it with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, adding osteopontin for amidation reaction, and after the reaction is completed, adding polyvinyl alcohol solution, nano-hydroxyapatite, bone morphogenetic protein-2 and adipic acid dihydrazide in sequence, and mixing evenly to obtain the precursor solution.

[0014] Further, in step two, the concentration of the hyaluronic acid solution is 3-8 g / 100mL, the concentration of the polyvinyl alcohol solution is 3-8 g / 100mL, the final concentration of the nano-hydroxyapatite is 1-3 g / 100mL, and the final concentration of bone morphogenetic protein-2 is 40-60 ng / mL; in step three, the crosslinking conditions are crosslinking at 35-37℃ for 2-3 hours.

[0015] The third aspect is to provide the application of the aforementioned stress-activated bone biomimetic stem cell delivery composite hydrogel in the preparation of medical materials for treating bone defects.

[0016] The present invention adopts the above technical solution and has the following technical effects compared with the prior art: This invention constructs a "neutral microgel-osteogenic matrix" separable structure, pre-protecting MSCs within microgel compartments with adjustable membrane properties. This effectively avoids cell damage caused by cross-linking agents, shear stress, and premature differentiation signals, which are present in traditional direct encapsulation methods. It significantly maintains high MSC activity during static storage and early implantation. Upon mechanical stimulation, the microgel membrane ruptures responsively, releasing MSCs in situ, achieving spatiotemporal separation and synergy between cell protection and in situ delivery.

[0017] The thickness and crosslinking density of the microgel membrane of this invention can be precisely controlled by adjusting the dispersed phase flow rate and crosslinking residence time during the preparation process, thereby allowing the microgel's rupture stress threshold to be designed as needed within the range of 15-100 kPa. This stress threshold range precisely covers the physiological hydrostatic pressure and mechanical stimulation levels sensed by cells during bone repair, enabling internal MSCs to be activated and released in a mechanical environment that matches the callus healing and hardening process. This utilizes the physiological load of the defect area as a trigger signal to transform the mechanical microenvironment into a regenerative signal that promotes repair.

[0018] In vitro experiments demonstrated that, under cyclic compression load stimulation simulating physiological stress, the MSCs encapsulated in the composite hydrogel of this invention exhibited significantly enhanced alkaline phosphatase activity and calcified mineral deposition compared to the direct encapsulation group without microgel protection. This indicates that the stress-activated delivery system, while protecting cells from initial adverse factors, can respond to mechanical stimulation to release MSCs and synergistically enhance their osteogenic differentiation potential and matrix mineralization capacity, significantly improving the osteogenic differentiation potential of MSCs and demonstrating significant application prospects in the regeneration and repair of critical bone defects. Attached Figure Description

[0019] Figure 1 The following are the characterization results of the neutral microgels of the present invention; wherein, A is the morphology of the microgels under bright field; B is the particle size distribution of the microgels; and C is a depth profile of the microgels containing mesenchymal stem cells after live / dead staining treatment.

[0020] Figure 2 The following are the characterization results of the stress-activated composite hydrogel scaffold of the present invention; wherein, A is the macroscopic morphology of the scaffold; B is a scanning electron microscope (SEM) image; C is the elemental distribution map of C, N, O, Ca and P; D is the Fourier transform infrared spectrum; and E is the Raman spectrum.

[0021] Figure 3 The results represent the stress response release performance characterization of the composite hydrogel. Among them, A is a time-series observation diagram of stress-triggered microgel rupture and release and diffusion of internal sodium fluorescein into the osteogenic matrix during 0~10s cyclic compression; B is a microscopic morphology comparison diagram of the uniform dispersion and stable retention of dye-labeled microgels in the osteogenic matrix under static conditions; C is a macroscopic comparison diagram of the release and redistribution of dye contents in the microgel before and after mechanical stimulation in the test tube system.

[0022] Figure 4 The results of the in vitro biocompatibility assessment of HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM were presented.

[0023] Figure 5 The study evaluated the osteogenic differentiation and mineralization performance of stem cells induced by each group of materials. A represents the qualitative staining results of ALP in each group; B represents the qualitative staining results of ARS calcium deposition in each group; C represents the quantitative statistics of ALP activity; and D represents the quantitative statistics of ARS mineralization level. ** indicates P < 0.01, indicating extremely significant differences between groups; ns indicates no statistical difference. Detailed Implementation

[0024] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, but this is not intended to limit the invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.

[0025] Experimental methods in the following examples, unless otherwise specified, were performed under standard conditions or as recommended by the manufacturer. Unless otherwise stated, all reagents and materials used in the following examples were commercially available.

[0026] Example 1 This embodiment provides a stress-activated bone biomimetic stem cell delivery composite hydrogel, the specific preparation method of which is as follows: Step 1: Preparation of neutral microgels (NM) containing MSCs Sodium alginate was dissolved in deionized water to prepare a 2.5 g / 100 mL solution, which was then aseptically filtered. For cell-loaded microgels, 1×10 8 Mesenchymal stem cells (MSCs) were resuspended in PBS and uniformly mixed with sodium alginate solution to obtain a cell-sodium alginate suspension. For the blank microgel used for physicochemical characterization, an equal volume of PBS was used instead of the cell suspension. The suspension was extruded at a set flow rate into a cross-linking bath containing a 50 mM Ca-EDTA complex using a microfluidic device, utilizing the dynamic equilibrium of the complex to slowly release Ca. 2+ This process triggers mild and controllable in-situ ionic crosslinking of sodium alginate, forming uniformly coated microgels. By adjusting the dispersed phase flow rate and the residence time of the microgels in the crosslinking bath, microgels with different film thicknesses and crosslinking densities were prepared. In this example, three groups were prepared: Group G1 with a flow rate of 50 μL / min and a residence time of 30 s; Group G2 with a flow rate of 50 μL / min and a residence time of 60 s; and Group G3 with a flow rate of 100 μL / min and a residence time of 60 s. After crosslinking, the microgels were thoroughly washed with PBS (pH 7.4), centrifuged at 500 g for 5 minutes, and collected to obtain neutral microgels.

[0027] Step 2: Preparation of osteogenic bone matrix precursor (HA-OPN-PVA-nHA-BMP-ADH) A 5 g / 100 mL hyaluronic acid (HA) solution was prepared in phosphate-buffered saline (PBS). 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS) were added to a final concentration of 5 mM, and the solution was activated at room temperature for 15 minutes. Recombinant osteopontin (OPN, 10 µg / mL) was added to the activated hyaluronic acid solution to promote the direct formation of an amide bond between the primary amine of OPN and the carboxyl group of hyaluronic acid. An equal volume of 5 g / 100 mL polyvinyl alcohol (PVA) solution was added and stirred until homogeneous. Nano-hydroxyapatite (nHA) was added to a final concentration of 2 g / 100 mL and bone morphogenetic protein-2 (BMP-2) to a final concentration of 50 ng / mL under stirring, and the mixture was dispersed thoroughly. To achieve cell-compatible chemical crosslinking without methacrylation or ultraviolet irradiation, adipic acid dihydrazide (ADH) was introduced into the remaining hyaluronic acid carboxyl group at a 1:1 molar ratio as a bifunctional crosslinking agent. After stirring evenly, a composite precursor solution was obtained.

[0028] Step 3: Construction of stress-activated composite hydrogels The neutral microgels (blank or loaded with MSCs) collected in step one were added at a mass ratio of 10% to the precursor solution of ADH that had just been mixed in step two but had not yet been crosslinked. The mixture was gently stirred at 45°C to ensure uniform dispersion of the microgels. The mixture was then injected into a mold and transferred to a 37°C environment for crosslinking for 2 hours. EDC / NHS-mediated covalent crosslinking of HA-ADH was completed, and the microgels were completely fixed within the osteogenic matrix, thus obtaining the stress-activated bone biomimetic stem cell delivery composite hydrogel.

[0029] The physical structure and mechanical response of the neutral microgels and composite hydrogels prepared by the above method were characterized: Microgel morphology and particle size: Under an optical microscope, the neutral microgels were observed to be regular spherical in shape and uniform in size. Figure 1 (A) The particle size histogram shows a narrow distribution centered on the target diameter. Figure 1 (B) Depth profile of a microgel containing mesenchymal stem cells after live / dead staining treatment. Figure 1 (C) shows that mesenchymal stem cells were successfully and uniformly embedded inside the three-dimensional structure of the microgel.

[0030] Film thickness measurement: Microgel resin embedded sections from each group were taken and the wall thickness was measured by confocal microscopy (n≥50 for each group). The results are shown in Table 1. The film thicknesses of G1, G2, and G3 were 8.2±0.72μm, 15.6±1.17μm, and 24.3±1.84μm, respectively, which increased with increasing flow rate and crosslinking time.

[0031] Compression fracture threshold: Each group of microgels was dispersed in 1% low-melting-point agarose to prepare cylindrical specimens. A compressive load was applied at a rate of 0.1 mm / s on a universal testing machine, and the fracture stress was recorded (n=6 per group). The results are shown in Table 1. The fracture stresses of G1, G2, and G3 were 15.4±1.62 kPa, 31.2±2.76 kPa, and 62.8±4.11 kPa, respectively. It can be seen that this invention can precisely control the fracture threshold within the range of 15-100 kPa by adjusting the preparation parameters, which matches the range of physiological hydrostatic pressure stimulation sensed by cells in bone repair (this mechanical stimulation can activate osteogenic differentiation-related signaling pathways in MSCs (RUNX2, OPN, etc.) and promote bone formation).

[0032] Table 1

[0033] Osteogenic matrix structure: The scaffold macroscopically presents as a continuous hydrated cylinder ( Figure 2 (A). Scanning electron microscopy reveals an interconnected porous network and truss-like wall structure. Figure 2 (B), this structure supports cell invasion, nutrient diffusion, and matrix deposition. Elemental mapping revealed a uniform distribution of C, N, O, Ca, and P ( Figure 2 (C), confirming the organic-inorganic composite composition. Fourier transform infrared spectroscopy and Raman spectroscopy show characteristic peaks of HA / OPN, PVA, nHA, BMP-2, and the signal of ADH crosslinked amide bonds (C). Figure 2 (D, E).

[0034] Stress-activated rupture behavior: Microgels loaded with sodium fluorescein were embedded in the osteogenic matrix and subjected to cyclic compression on a confocal microscope mechanical loading stage. It was observed that the microgel membrane ruptured upon reaching the deformation threshold, releasing its contents and diffusing into the surrounding hydrogel matrix, confirming the stress-sensitive mechanical design. Figure 3 (A). Dye-based observations showed that the microgels were uniformly dispersed in the osteogenic matrix and remained stably within the matrix network under static conditions. Figure 3 (B). In in vitro experiments, spatial redistribution and release of the contents of the dye-labeled microgels were also observed after mechanical stimulation. Figure 3 (C), further confirming that the composite hydrogel possesses a sensitive stress-responsive release function.

[0035] Example 2: In vitro cell experiments of stress-activated composite materials 1. Cell compatibility evaluation Bone marrow-derived mesenchymal stem cells (MSCs) were harvested and neutral microgels loaded with MSCs were prepared under the G3 conditions (rupture stress approximately 62.8 kPa) as described in Example 1. The microgels were then cross-linked with osteogenic matrix precursors to obtain the HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM scaffold. Three control groups were established: ① Control group (HA-PVA-ADH hydrogel); ② HA-OPN-PVA-nHA-BMP-ADH group (osteogenic matrix, cell-free); ③ HA-OPN-PVA-nHA-BMP-ADH-MSCs group (equal amounts of MSCs were directly mixed into the osteogenic matrix precursors for cross-linking, without microgel protection).

[0036] Each scaffold group was placed in osteogenic induction medium and cultured at 37°C and 5% CO2. For the HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM group scaffolds, cyclic compression loading (20% strain amplitude, 1 Hz frequency, 30 min duration) was applied daily using a dynamic mechanical analyzer during culture to simulate the physiological stress microenvironment and trigger in-situ rupture of the microgel membrane and release of MSCs; the remaining groups were statically cultured under the same conditions. Cell viability was assessed using the CCK-8 assay at 1 and 3 days of culture.

[0037] The results are as follows Figure 4 As shown, cell viability assays indicate that the HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM scaffold has good biocompatibility.

[0038] 2. Assessment of osteogenic differentiation and mineralization Each scaffold was placed in osteogenic induction medium and cultured at 37°C and 5% CO2. For the HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM scaffold, cyclic compression loading (20% strain amplitude, 1 Hz frequency, 30 min) was applied daily using a dynamic mechanical analyzer during the culture period to simulate the physiological stress microenvironment and trigger in-situ rupture of the microgel membrane and release of MSCs; the other groups were statically cultured under the same conditions. Alkaline phosphatase (ALP) staining and relative ALP activity assays were performed on day 14 to evaluate early osteogenic differentiation; Alizarin Red (ARS) staining and relative ARS activity assays were performed on day 21 to evaluate calcified mineral deposition.

[0039] The results are as follows Figure 5As shown, compared with the control group, the osteogenic matrix group exhibited significantly increased ALP activity and calcium deposition (P<0.01), confirming the osteogenic induction capabilities of nHA and BMP-2. There was no statistically significant difference (ns) in ALP and ARS indices between the directly encapsulated MSCs group and the osteogenic matrix group. However, the HA-OPN-PVA-nHA-BMP-ADH-MSCs-NM group showed the highest ALP activity and calcium mineralization deposition, both significantly higher than the directly encapsulated MSCs group (P<0.01). This indicates that the stress-activated microgel system can effectively protect and responsively release MSCs, significantly enhancing their osteogenic differentiation potential and matrix mineralization capacity.

[0040] The above description is merely a preferred embodiment of the present invention and does not limit the implementation and protection scope of the present invention. Those skilled in the art should realize that any equivalent substitutions and obvious changes made based on the content and illustrations of the present invention should be included within the protection scope of the present invention.

Claims

1. A bone biomimetic stem cell delivery composite hydrogel, characterized in that, Include: Osteogenic bone mimicry matrix is ​​a hydrogel with a cross-linked network structure. The osteogenic bone mimicry matrix is ​​formed by cross-linking hyaluronic acid modified with osteopontin and adipic acid dihydrazide through amide bonds to form a cross-linked network. Polyvinyl alcohol is physically entangled in the cross-linked network and the network structure is further stabilized by hydrogen bonds. Nano-hydroxyapatite and bone morphogenetic protein-2 are dispersed and loaded in the cross-linked network. And neutral microgels dispersed within the osteogenic bone-simulating matrix; The neutral microgel is a membrane-structured microsphere formed by ionic cross-linking of sodium alginate, which carries mesenchymal stem cells and is configured to rupture upon exposure to mechanical stress exceeding the compression rupture threshold of the neutral microgel, thereby releasing the mesenchymal stem cells; the membrane thickness of the neutral microgel is 8-25 μm, and the compression rupture threshold is 15-100 kPa. The neutral microgel is prepared by: extruding a mixed suspension of sodium alginate solution and mesenchymal stem cell suspension into a cross-linking bath containing Ca-EDTA complex through a microfluidic device, forming a neutral microgel containing mesenchymal stem cells through ionic cross-linking, and then washing and centrifuging to collect it. The concentration of the sodium alginate solution is 2.0-3.0 g / 100 mL, the flow rate of the dispersed phase extruded by the microfluidic device is 50-100 μL / min, and the residence time in the crosslinking bath is 30-60 s, so as to control the film thickness and compression rupture threshold of the neutral microgel.

2. The bone biomimetic stem cell delivery composite hydrogel according to claim 1, characterized in that, The neutral microgel constitutes 5-15% by mass in the osteogenic bone-simulating matrix.

3. A method for preparing a bone biomimetic stem cell delivery composite hydrogel as described in any one of claims 1-2, characterized in that, Includes the following steps: Step 1, Preparation of neutral microgels: The mixed suspension of sodium alginate solution and mesenchymal stem cell suspension is extruded into a cross-linking bath containing Ca-EDTA complex through a microfluidic device, and neutral microgels containing mesenchymal stem cells are formed through ionic cross-linking. The microgels are then washed, centrifuged and collected. Step 2: Prepare osteogenic bone-simulating matrix precursor solution; Step 3, constructing the composite hydrogel: disperse the neutral microgel collected in Step 1 in the osteogenic bone-mimicking matrix precursor solution in Step 2, inject it into a mold, and cross-link it to form the bone biomimetic stem cell delivery composite hydrogel.

4. The preparation method according to claim 3, characterized in that, In step two, the preparation of the osteogenic bone matrix precursor solution includes: preparing a hyaluronic acid solution in phosphate buffered saline, activating it with 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide, adding osteopontin for amidation reaction, and after the reaction is completed, adding polyvinyl alcohol solution, nano-hydroxyapatite, bone morphogenetic protein-2 and adipic acid dihydrazide in sequence, and mixing them evenly to obtain the precursor solution.

5. The preparation method according to claim 4, characterized in that, In step two, the concentration of the hyaluronic acid solution is 3-8 g / 100mL, the concentration of the polyvinyl alcohol solution is 3-8 g / 100mL, the final concentration of the nano-hydroxyapatite is 1-3 g / 100mL, and the final concentration of the bone morphogenetic protein-2 is 40-60 ng / mL; in step three, the crosslinking conditions are crosslinking at 35-37℃ for 2-3 hours.

6. The use of the bone biomimetic stem cell delivery composite hydrogel as described in any one of claims 1-2 in the preparation of medical materials for treating bone defects.

Citation Information

Patent Citations

  • Injectable bone-repairing hydrogel containing exosomes of human umbilical cord mesenchymal stem cells and preparation method of injectable bone-repairing hydrogel

    CN112206356A

  • Injectable bone constructed based on injectable hydrogel scaffold material and application of injectable bone

    CN115702952A